Two zinc(ii)-based coordination polymers with flexible dicarboxylate and pyridine mixed ligands: effect of π⋯π interactions on electrical activity. (1st October 2019) - Akhtaruzzaman,; Das, Pubali; Khan, Samim; Maity, Suvendu; Naaz, Sanobar; Islam, Sakhiul; Ghosh, Prasanta; Ray, Partha Pratim; Mir, Mohammad Hedayetullah
Abstract : We synthesized two Zn(ii )-based 1D coordination polymers with paddle-wheel units using flexible 1, 4-cyclohexanedicarboxylate linkers; these compounds exhibited electrical conductivity and Schottky barrier diode behavior. Abstract : Two novel coordination polymers (CPs) [Zn( cis -1, 4-chdc)(4-phpy)] n, (1 ) and [Zn( cis -1, 4-chdc)(py)] n, (2 ) (1, 4-H2 chdc = 1, 4-cyclohexanedicarboxylic acid, 4-phpy = 4-phenylpyridine and py = pyridine) were synthesized and characterized by elemental analysis, infrared spectroscopy, single-crystal X-ray diffraction, powder X-ray diffraction and thermogravimetric analyses. Both compounds formed a one-dimensional (1D) chain-like structure constructed by Zn2 (CO2 )4 paddle-wheel dimers interconnected via double strands of cis -1, 4-chdc-bridges, whereby pyridine-based ligands were decorated as arms on both sides of Zn2 dimers. In compound 1, polymeric 1D chains underwent self-assembly via π⋯π stacking interactions among 4-phpy ligands to form a 2D network, whereas this type of interaction was absent in 2 . Interestingly, both compounds exhibited electrical conductivity and revealed Schottky barrier diode behavior. However, compound 1 showed better electrical conductivity (1.09 × 10 −3 S m −1 ) with respect to compound 2 (6.01 × 10 −5 S m −1 ) because of π⋯π interactions.